PENGOLAHAN CITRA FOTO SINAR-X UNTUK MENDETEKSI KELAINAN PARU - Tri Watiningsih (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2012)
AbstractUntil now, pdentification of the lung disorder on X-ray photos was done using manual methode so that it is necessary to make an identification using image analysis. This methode was introduced to make medical practitioners easear to indentify the lung disorder computerizedly. The purpose of this study is to prove that dpgital image analysis can be used to identify the lung disorder on X-rays photo.Image analisis performed in this study, consisst several methode of image preprocessing until an image was prepared to be processed. Image preprocessing contain intensity adjustment and histogram equalization, until an image obtained was prepared to be further processed.The results of this are the following : (a) the subjective level of identification process on the lung can be degraded using application software for analyzing image of X-ray photos whichhad been developed during the research, (b) the conventional adge detection on image has a lack of ability to identify interested lung image boundaries which have more than one with variated gradation of grey levels, (c) the combination of histogram equalization and dilation of image edges gives adequately significant information on identifications process, covulution the application of software for analyzing image of X-ray hpotos witch had been developed during the research has an ability to assist medical radiology practptioners to explore the informations. Keywords : identification, histogram equalization, contrast stretching, intensity adjustment.